IMPLEMENTASI METODE FORWARD CHAINING DALAM SISTEM PAKAR UNTUK MENDETEKSI KERUSAKAN JARINGAN LOCAL AREA NETWORK (LAN) - Mas’ud, Huzaima; Muthia, Muthia (Diffusion: Journal of Systems and Information Technology, 2024)
The implementation of forward chaining method in an expert system for detecting Local Area Network (LAN) damages is explored in this study. The forward chaining method, a reasoning strategy commonly employed in expert systems, is utilized to infer potential network failures based on observed symptoms and known network configurations. The expert system aims to aid users and network specialists in diagnosing LAN issues efficiently and accurately. Through the forward chaining mechanism, the system iteratively analyzes symptoms provided by users and matches them with predefined rules to deduce possible network damages. The system's effectiveness is evaluated based on its ability to accurately identify and diagnose LAN problems, thereby facilitating prompt troubleshooting and maintenance. The findings of this research contribute to the advancement of expert systems in the field of network diagnostics and maintenance, providing valuable insights into the practical application of forward chaining method in LAN damage detection.